(untitled) (Journal of the College of Education for Women, 2019)
The Research aims to understand Student’s attitudes towards AcademicCheating in the Technical College -Baghdad. The study was made on a sample of(88) students in the fourth (final) year who were randomly selected from the everyscientific department in the college. The researchers prepared academic cheating aquestionnaire. The research results showed that. The results showed that there is astrong trend among the students to reject the cheating phenomenon. ( 72.72%) ofthe specimen groups do not see that there is a justification in cheating, on the otherhand the results determined the means and reasons for the cheating by the studentsand the negative outcome of that phenomenon.